Synthetic Augmented Suture Anchor Reconstruction for a Complete Traumatic Distal Triceps Tendon Rupture in a Male Professional Bodybuilder with Postoperative Biomechanical Assessment. (16th February 2014) - Nikolaidou, Maria-Elissavet; Banke, Ingo J.; Laios, Thomas; Petsogiannis, Konstantinos; Mourikis, Anastasios
Abstract : Bodybuilding is a high-risk sport for distal triceps tendon ruptures. Management, especially in high-demanding athletes, is operative with suture anchor refixation technique being frequently used. However, the rate of rerupture is high due to underlying poor tendon quality. Thus, additional augmentation could be useful. This case report presents a reconstruction technique for a complete traumatic distal triceps tendon rupture in a bodybuilder with postoperative biomechanical assessment. A 28-year-old male professional bodybuilder was treated with a synthetic augmented suture anchor reconstruction for a complete triceps tendon rupture of his right dominant elbow. Postoperative biomechanical assessment included isokinetic elbow strength and endurance testing by using multiple angular velocities to simulate the "off-season" and "precompetition" phases of training. Eighteen months postoperatively and after full return to training, the biomechanical assessment indicated that the strength and endurance of the operated elbow joint was fully restored with even higher ratings compared to the contralateral healthy arm. The described reconstruction technique can be considered as an advisable option in high-performance athletes with underlying poor tendon quality due to high tensile strength and lack of donor site morbidity, thus enabling them to restore preinjury status and achieve safe return to sports.